Inhibition effect of eco-friendly curcumin based Schiff base on industrially important mild steel material corrosion: Electrochemical and quantum chemical evaluation - N. Ashwini; R. Dileep; S. Ranganatha (Results in Surfaces and Interfaces)
The corrosion inhibition effect of a curcumin based eco-friendly Schiff base, 2-Amino [(curcumin)-5-bromo]-pyridine (ACBP) on mild steel in 1 M HCl has been studied by gravimentric and electrochemical techniques such as potentiodynamic polarization and electrochemical impedance spectroscopy. Corrosion studies show that inhibition efficiency of the synthesized molecules are sensitive for it's concentration. Inhibitor adsorption studies were carried out at different temperature which revealed that the process being exothermic obeying Langmuir's isotherm. Gravimentric experiments pronounce the similar corrosion trends with varied concentrations of the inhibitors. Based on quantum chemical parameters, mechanism of adsorption and thus the inhibition has been proposed.